Do Financial Knowledge and e-Payment Awareness Affect Saving and Spending Behavior? The Mediating Role of Financial Risk Tolerance - Dewi, Vera Intanie; Effendi, Nury; Ervani, Eva; Sapulette, Militcyano Samuel (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
This study investigates the role of financial risk tolerance in mediating the impact of financial knowledge and e-payment awareness on saving and spending behavior. A total of 400 questionnaires were distributed, with 396 completed by respondents and used for analysis. This research employs partial least squares-based structural equation modeling (PLS-SEM) to validate and estimate the proposed research models, with Smart- PLS software analyzing the data and estimating the relationships between its latent variables. Our study’s estimation provides evidence of the positive and significant role of financial risk tolerance in mediating the impact of financial knowledge and e-payment awareness on spending and saving behavior. This study also reveals differences in the level of financial risk tolerance between male and female participants. Furthermore, the analysis results indicate that most younger people have a risk tolerance level (i.e., risk profile) that falls into the medium (i.e., risk-averse) category in terms of risk speculation, invest- ment risk, and financial risk evaluation.